A review of Ancient Roman water supply exploring techniques of pressure reduction. - Monteleone, M. C.; Yeung, Hoi; Smith, Richard (IWA Publishing, 2007)
The Ancient Roman water supply systems still leave us astonished when admiring the solidity of the ruins of aqueducts surviving around Europe. Some parts of these systems are still in use at present and prove the practical efficiency of Roman hydraulics in the principles acquired from the populations living in the different regions of the Empire. In Pompeii the urban water supply system stands as a clear example of the Roman planning of urban complex networks by using small water towers to serve a limited numbers of users. This allowed to control the derivations and their maintenance and operated a disconnection from the high pressure mains and the low pressure pipes, maintaining a fixed maximum height of water over the final points of discharge. Considering the techniques for pressure reduction as a method to control leakages, this paper examines the ancient Roman water supply system to deduce some applications to modern urban networks built in new housing establishments.
Keywords: Low pressure water supply systems; pressure control; Roman water supply